2022
DOI: 10.1186/s12905-022-02059-4
|View full text |Cite
|
Sign up to set email alerts
|

HIV is still a major public health problem among pregnant women attending ANC in Referral Hospitals of the Amhara Regional State, Ethiopia: a cross sectional study

Abstract: Background The burden of HIV is disproportionately higher among women of reproductive age contributing more than half of the global share. The situation in Ethiopia is not exceptional. The present study was done to determine the proportion of HIV among pregnant women in Amhara Regional State, Ethiopia. Method Institutions-based cross-sectional study was conducted from October 2020 to December 2020. Systematic random sampling technique was used to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Particularly, pregnant women with HIV (accounting for about 18% of those infected) are a primary concern in the province's HIV prevention campaign due to the substantial risk of transmitting HIV to future generations if the province does not implement any action programs to combat this dangerous epidemic. 11,12 We chose the year 2010 to investigate the rate of pregnant women infected with HIV because in 2010, the entire An Giang province implemented comprehensive HIV counseling and testing, and voluntary HIV testing for all pregnant women coming for prenatal check-ups and childbirth. We found that the rate of pregnant women infected with HIV in An Giang province was 0.29%.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, pregnant women with HIV (accounting for about 18% of those infected) are a primary concern in the province's HIV prevention campaign due to the substantial risk of transmitting HIV to future generations if the province does not implement any action programs to combat this dangerous epidemic. 11,12 We chose the year 2010 to investigate the rate of pregnant women infected with HIV because in 2010, the entire An Giang province implemented comprehensive HIV counseling and testing, and voluntary HIV testing for all pregnant women coming for prenatal check-ups and childbirth. We found that the rate of pregnant women infected with HIV in An Giang province was 0.29%.…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative approach of this study also revealed that pregnant women with a history of known chronic illness were 57.1% less likely to initiate ANC visit early than their counterparts, which is not in line with any previous undertaking. Appreciating the fact that more than 12% of those pregnant women were patients leaving with HIV who did not want to disclose their status, for which they took, even, their medication from other distant ART sites; they may not early present themselves to the nearby health facilities, where they think their status will no longer be confidential [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This technique stimulates a broader repository of T cells compared to peptide-antigen-loaded DCs, generating T cells specific to known and unidentified TAA epitopes presented by different HLA types. Generic stimulation of T cells potentially benefits larger patient populations, making DC therapy an effective procedure for mRNA transfection, either in vivo or ex vivo [ 66 ].…”
Section: Reviewmentioning
confidence: 99%